Simulation Study of BPPV Fatigability - Yang, Xiaokai; Gao, Lidan (Frontiers in Neurology, 2022)
To analyze the mechanism and clinical significance of Benign paroxysmal positional vertigo (BPPV) fatigability and discuss how to eliminate BPPV fatigability. A physical simulation model of BPPV was developed to observe the effect of the Dix-Hallpike test on otolith location and explore strategies to eliminate fatigability. Dix-Hallpike test can keep the otoliths in the lower arm of the posterior semicircular canal away from the ampulla. When the head is tilted 30° forward, the otolith slides to the lower arm near the ampulla, which is sufficient to ensure that the starting position of the otolith is consistent when the Dix-Hallpike test is repeated. When the head is tilted 60° forward, the otolith can enter the ampulla and reach the bottom of the crista ampullaris, which leads to long latency because the otolith sliding in the ampulla does not cause an obvious hydrodynamic effect during the Dix-Hallpike test. The otoliths located on the short arm side of the posterior semicircular canal will break away from the short arm side and enter the utricle when the head is tilted 120° forward. The stable and consistent nystagmus induced by the improved diagnostic test may be a more important feature of BPPV.